Use of 8-mm and 9-mm implants in atrophic alveolar ridges: 10-year results - Mertens, Christian; Bäumer, Amelie; Kappel, Hannes; Hoffmann, Jürgen; Steveling, Helmut (The international journal of oral & maxillofacial implants, 2012)
PURPOSE: The use of short implants can reduce the need for augmentative procedures prior to implant placement and, thus, morbidity and treatment time for patients with severely atrophied alveolar ridges. However, the inevitably less favorable crown-to-implant ratio is often associated with higher implant failure rates and greater marginal bone loss. The aim of this study was to evaluate the long-term survival and success rates of short implants in severely atrophic alveolar ridges retaining restorations on these short implants only. MATERIALS AND METHODS: In this study, 8-mm and 9-mm implants were inserted in atrophic alveolar ridges according to the manufacturer's protocol for the respective bone quality and loaded after 3 months of healing. Prosthetic restorations were supported only by short implants (not in combination with longer implants). After a mean observation period of 10.1 years (±1.9 years), all patients were re-examined clinically and radiographically. RESULTS: In this study, fifty-two 8-mm and 9-mm implants were placed in 14 patients. After 10.1 years, no implants and suprastructures had been lost. A mean marginal bone loss of 0.3 mm (±0.4 mm) was recorded. According to the Albrektsson criteria, all implants were successful; with respect to the more rigorous Karoussis et al criteria, four implants failed. CONCLUSIONS: The results of this long-term study suggest that the use of short implants results in marginal bone resorption and failure rates similar to those for longer implants. The higher crown-to-implant ratio did not seem to have any negative influence on implant success in this study.